Improving the metabolisable energy value of brewers' dried grains with enzyme cocktails in poultry nutrition - Jimoh Abdulhameed; Atteh Job O. (Journal of Agricultural Sciences (Belgrade), 2018)
The determination of the positive effects of exogenous enzymes is essential to ensure their inclusion in poultry feed formulation. This study was conducted to determine the effect of enzymes on the apparent metabolisable energy (AME) value of brewers' dried grain (BDG). Xylanase, phytase and multipurpose enzymes were used in a completely randomised design to determine the effects of individual exogenous enzymes and their cocktails on poultry metabolisable energy using adult cockerels. There were eight treatments comprising a control and seven experimental treatments with BDG and one, two or three enzymes. The AME values were determined using the intubation method. Data collected were analysed using the statistical analysis system. Enzymes individually and as a cocktail improved the AME value of BDG compared to the control. An increase in the AME value was 3.48%, 5.39%, 5.92%, 14.29%, 18.13%, 23.21% and 29.58% respectively for phytase, xylanase, cocktail of xylanase and phytase, multipurpose enzyme, cocktail of multipurpose enzyme and phytase, cocktail of xylanase and multipurpose enzyme and cocktail of xylanase, phytase and multipurpose enzyme. Cocktails of enzymes were significantly better (P˂0.05) than individual enzymes in their effects on apparent metabolisable energy of BDG. Phytase gave a marginal increase in AME of the studied feedstuff. It has been concluded that the cocktail of enzymes is better than individual enzymes in their effects on AME of BDG. If different enzymes are available, it is recommended that the enzyme with higher units should be used.